Biomass Co-Firing for Electricity in Indonesia: A System Thinking Approach - Raisa Zakia; Yos Sunitiyoso (Green Publisher Indonesia, 2025)
Indonesia's heavy reliance on coal for electricity generation poses significant environmental challenges, necessitating a transition toward more sustainable energy sources. Biomass co-firing, which involves blending biomass with coal in existing power plants, offers a practical solution to reduce carbon emissions while utilizing the country's abundant biomass resources. However, its large-scale implementation is influenced by multiple interdependent factors, including fuel availability, economic feasibility, technological readiness, and policy support. The study utilizes qualitative data analysis which is collected on interview sessions with energy and electricity stakeholders, including government, national electricity producers, and biomass suppliers. The study found 44 factors influence the system of biomass co-firing for electricity, which derived from seven categories, including biomass related factors, economic feasibility, government, institutional characteristics, technical practicality, and new renewable energy/bioenergy. The interrelationships within the factors were analyzed using causal loop diagrams, which include three major drivers, which are technical practicality, institutional characteristic, and economic feasibility. The findings emphasize the need for coordinated policies, investment in biomass supply chains, and stakeholder collaboration to enhance co-firing effectiveness. This study contributes to the understanding of biomass integration in the electricity sector and offers strategic recommendations to accelerate Indonesia’s sustainable energytransition